Experimental investigation into the post-breakage performance of pre-cracked laminated glass plates. (10th November 2019) - Zhao, Chenjun; Yang, Jian; Wang, Xing-er; Azim, Iftikhar
Highlights: A series of damaged laminated glass (LG) plates were tested on their post-breakage performance. The post-breakage stiffness, resistance and the failure modes of structural LG plates are provided. The key influencing factors on the post-breakage behavior of LG were identified and analyzed. The hybrid configuration including annealed glass and PVB will improve post-breakage behavior. Abstract: SentryGlas® (SG) laminated glass (LG) is commonly used as a load bearing material in structural applications. Like other conventional structural materials, SG LG plates are expected to have adequate stiffness and resistance to breakage so that they can withstand loads from either external action or their self-weight. This paper reports an experimental study of the post-breakage behaviour of SG LG plates. In the study, a weight-drop impact load was first applied to crack glass plates to create a crack pattern under hard-body impact. These cracked glass plates were subsequently subjected to a continuous static load until collapse. The applied load and the deflections at seven reference points on the specimens were recorded and examined. Two key parameters, the initial stiffness and the peak post-breakage resistance, were identified to evaluate the post-breakage performance of seven groups of specimens. The effects of glass make-up and the support condition were observed and are discussed. It was found that the support condition determines the load transfer path and further influences the 'yield line' pattern and post-breakage resistance. It was also observed that the different crack patterns created various load bearing mechanisms and the glass make-up also played an important role in the post-breakage resistance and the failure mode. Experimental results reveal that the annealed glass (ANG) sheet yields the highest initial stiffness and resistance in the post-breakage phase. With an increasing number of SG interlayers, the LG plate is more likely to be penetrated before the 'yield lines' completely form. Finally, a comparison study was carried out to investigate the post-breakage performance. Results indicate that in comparing ANG and the fully tempered glass (FTG) plates, the former exhibits a better ability in retaining the post-breakage capacity.